2020
DOI: 10.1186/s13287-020-01707-6
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicle-encapsulated miR-22-3p from bone marrow mesenchymal stem cell promotes osteogenic differentiation via FTO inhibition

Abstract: Background: Bone marrow mesenchymal stem cells (BMSCs) exhibit the capacity to self-renew and differentiate into multi-lineage cell types, including osteoblasts, which are crucial regulators of fracture healing. Thus, this study aims to investigate the effect of microRNA (miR)-22-3p from BMSC-derived EVs on osteogenic differentiation and its underlying mechanism. Methods: Extracellular vesicles (EVs) were isolated from BMSCs and taken up with BMSCs. Dual-luciferase reporter gene assay was used to verify the bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 32 publications
4
71
0
Order By: Relevance
“…This indicates that alcohol affects osteogenic differentiation through altering exosomes, making miRNAs a very likely candidate for such effect. Previous studies have reported an association between elevated miRNA 22-3p levels and increased expression of RUNX2 and OCN [67]. Therefore, a decrease in miRNA 22-3p can lead to a decrease in these osteogenic markers, which was also observed in our experiments (Fig 5D).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This indicates that alcohol affects osteogenic differentiation through altering exosomes, making miRNAs a very likely candidate for such effect. Previous studies have reported an association between elevated miRNA 22-3p levels and increased expression of RUNX2 and OCN [67]. Therefore, a decrease in miRNA 22-3p can lead to a decrease in these osteogenic markers, which was also observed in our experiments (Fig 5D).…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, up-regulation of these miRNAs observed in our results ( Figs 3D and 4A) can inhibit osteogenic differentiation. In contrast, EV-encapsulated miRNA-22-3p from BMSCs have been shown to promote osteogenic differentiation in neighboring BMSCs and increase matrix mineralization [67]. Hence, the upregulation of miRNAs 25-3p and 214-3p as well as down-regulation of miRNA 22-3p all can lead to inhibition of osteogenic gene expression observed in Fig 5, prevent osteogenic differentiation, and cause the osteogenic deficits observed in FAE.…”
Section: Discussionmentioning
confidence: 95%
“…Osteoblast differentiation is also dependent on the regulation of FTO. Studies have shown that miR-22-3p and miR-149-3p modulate the osteoblast differentiation of BMSCs by targeting FTO (Li et al, 2019 ; Zhang et al, 2020 ). Mice with a global loss of FTO or a selective lack FTO in osteoblasts exhibit bone loss (Sachse et al, 2018 ; Zhang Q. et al, 2019 ).…”
Section: A Modification In Cells Involved In Rmentioning
confidence: 99%
“…These regulatory effects of lncRNAs have also begun to attract widespread attention 11 . Recent studies have shown that some lncRNAs are involved in regulating the adipose differentiation and osteogenic differentiation of BMSCs 12,13 . Studies have reported that LncRNA H19 can stimulate the osteogenic differentiation of BMSCs, while inhibiting the adipogenic differentiation of BMSCs 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…11 Recent studies have shown that some lncRNAs are involved in regulating the adipose differentiation and osteogenic differentiation of BMSCs. 12,13 Studies have reported that LncRNA H19 can stimulate the osteogenic differentiation of BMSCs, while inhibiting the adipogenic differentiation of BMSCs. 14,15 Our previous research results indicate that LncRNA H19 adsorbs miR-188 through the ceRNA mechanism and then mediates LCoR's influence on the osteogenic and adipogenic differentiation of mouse BMSCs, 15 but does LncRNA H19 pass externally?…”
Section: Introductionmentioning
confidence: 99%